SOCIO-ECONOMIC ASPECTS OF DEVELOPMENT OF SMALL INNOVATIVE BUSINESS IN RUSSIA - Anatolievich Doroshenko, Yuri (Journal of Applied Engineering Science, 2015)
This article describes the main components of creating an innovative product, found inter dependence of costs for research & development and patent activity in the country. It shows the comparative characteristics of small innovative business’s systems in the industrially advanced countries and Russia. The positive role of copying foreign production of innovative goods and the use of technology was identify. The basic socio-economic problems affecting the active development of innovative entrepreneurship were distinguished. Considered the Russian experience in the development of small and medium-sized enterprises in pre-revolutionary and Soviet times (artisanal-cooperative movement). Recommendations for the creation of innovation climate, based on the support of the invention and the mentality of the Russians were given in this article.